Membaharui Dunia Lewat Semangat Persaudaraan Global - Hendro Setiawan (Mitra Sriwijaya: Jurnal Teologi dan Pendidikan Kristen, 2020)
The latest Pope Francis encyclical entitled "On The Fraternity and Social Friendship" (Fratelli Tutti) was signed on October 3, 2020. This encyclical emerged as the world was struggling against the Covid 19 pandemic. This encyclical is considered a universal proposal and is proposed to improve the world. Global phenomena in the form of: social injustice, environmental damage, ineffective handling of the pandemic, and various other major problems, considered by the Pope as urgent to be reflected and renewed. Through this encyclical, the pope invites all parties, all religions, even atheists, to work together in creating a better world for everyone. Since the beginning of the pandemic, Pope Francis has reflected on the pandemic as a universal call to strengthen human fraternity. Pope invites all parties during the pandemic, to think about and prepare for a better world in the context of humanity. The world after the pandemic must be a world that is more welcoming to everyone without exception. It is hoped that a world that is more humane and in solidarity will be able to overcome the problems of humanity before The pope's initial thoughts are contained in his eight letters compiled in a book entitled Life After The Pandemic. The encyclical "On The Fraternity and Social Friendship" (Fratelli Tutti), which emerged afterward, is a concrete form of the pope's thinking about what is needed to reform the world today. What is the proposal like? Is it really relevant to renew the world? How can this be realized?